Academic Achievement in Children and Adolescents with Type 1 Diabetes: Tripoli University Hospital Experience, Libya - Noureddin Frewan, Asma; Hadeed, Ibtisam (Benghazi University Medical Journal, 2026)
Background: Type 1 diabetes (T1D) is a chronic disease affecting children and adolescents, which may impact their academic achievement. Objective: To evaluate the clinical impact of T1D on academic achievement in children and adolescents and compare scholastic achievement with their non-diabetic peers. Methods and Materials: A prospective case-control study was conducted in the Pediatric Endocrinology Department at Tripoli University Hospital between February and May 2025, after obtaining ethical approval and parental consent. The study included 120 Libyan children and adolescents with T1D, aged 6–18 years, who were enrolled in formal schooling. Data on demographics, disease characteristics, glycemic control, and academic achievement were collected. Statistical analyses assessed associations between variables. Results: Good glycemic control (HbA1c 6–8%) was observed in 55% of patients and was strongly associated with better academic achievement (P = 0.001). Children with well-controlled diabetes demonstrated academic achievement similar to that of their non-diabetic peers. Conversely, non-diabetic children achieved significantly higher mean grades than diabetic children with poor glycemic control. No significant associations were found between academic achievement and age, gender, or age at disease onset, including onset before school entry (P > 0.05). Parental education was significantly associated with academic achievement (father: P = 0.008; mother: p = 0.001). Factors significantly associated with glycemic control included hypoglycemia frequency (p = 0.030), hospital admissions (p = 0.046), ICU admissions (P = 0.02), and treatment modality (p = 0.001). Chronic complications and associated diseases had no significant impact on academic achievement. Conclusion: Good glycemic control and effective diabetes management were associated with a better academic achievement. Parental education and treatment modality significantly influence glycemic control. T1D, in the absence of poor glycemic control, does not significantly impair academic achievement.